Sports Massage Therapy to Overcome Fatigue Problems in Nurses: a Literature Review - Prasetya, Fika Indah; Hartono, Soetanto; Wahyuni, Endang Sri; Muhammad, Heryanto Nur; Suryaningtyas, Eka; Nurvitasari, Rifzi Devi (IKIP Widya Darma Surabaya, 2024)
Objective: Workers often ignore the various aspects that can affect their work, health, and comfort caused by physical and mental fatigue. Hospital nurse fatigue is associated with lower nurse satisfaction, higher turnover, and poor patient outcomes. Fatigue is a common problem for nurses, with 82% of nurses experiencing mild to severe physical fatigue. There are many ways to combat fatigue symptoms and speed recovery after exercise, including massage techniques. It is believed that sports massage supplies oxygen to the muscles. As it circulates in the blood, lactic acid is converted to pyruvic acid, generating ATP, and activating muscle metabolism. This study aims to identify appropriate sports massage therapy to treat caregiver fatigue issues. Method: A literature review was used in this study. Article searches were performed in his six journal databases: PubMed, JSTOR, Taylor, Willey Online, Sage, and Google Scholar. Eight articles that met the inclusion criteria were found. Result: The results of this review indicate that sports massage techniques can be used as an alternative to reduce caregiver fatigue when providing community health services. Novelty: This study shows the effectiveness of sports massage therapy in overcoming and treating caregiver fatigue issues.